Male Writers of DānměiLiterature: An Analysis of Fēitiānyèxiáng - Wang, Aiqing (Center for Research and Development of Religious Literature and Heritage, 2021)
In this paper, I investigate dānměias a ground-breaking literary genre by means of scrutinising an illustrious male writer pseudonymed Fēitiānyèxiáng, and I propound that his works are exemplary as online writing. As a growing Chinese Internet literature, the female-oriented dānměigenre, aka Boys Love, has attracted legions of heterosexual fangirl producers and consumers as well as a meagre amount of their male counterparts. Among male dānměiwriters, who are in an absolute minority, Fēitiānyèxiángis celebrated fora wide range of innovative themes and magnificent storylines, and his fiction is replete with profound literary and historical allusionsand elaborate and meticulous depictions. Furthermore, notwithstanding a non-reversible bipartite dichotomy between seme (top) and uke (bottom)roles, Fēitiānyèxiáng’s writing is not featured by feminisation of uke, which is clichéd characterisation in not only the dānměi subculture, but also classical and modern Chinese literature. More significantly, Fēitiānyèxiáng’s narratives are reality-oriented, addressing adverse circumstances in a real-world context and hence rendering characters more multi-faceted, and he does not circumvent realistic issues or create over-romanticised representation, analogous to his equivalent pseudonymed Nánkāngbáiqǐ.